Going Circular: Indigenous Legal Research Methodology as Legal Practice - Hanna, Alan (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
Working in Indigenous communities evokes thoughts about appropriate research methodologies. The default to academic methodologies raises questions about what Indigenous research methodologies might look like. Although there is growing discourse on this subject, I often wonder why Indigenous methodologies still tend to follow Western academic approaches. In this paper, I explore possibilities for alternative ways of understanding Indigenous research methodologies that are aligned with Indigenous practices. I argue that when research is conducted according to the ways and worldview of a particular Indigenous group, the researcher will find themselves practising the laws of that society, as many legal principles are exhibited through the manner in which a person walks in the world. Legal research specifically invites and encourages researchers to work in accordance with the very principles being learned. A methodology arising from a particular worldview and the legal order that it entails will promote practices long entrenched in its communities. Walking in such a manner allows a person to break free from traditional Western methodologies and begin to see the world through the cyclical movements of Indigenous knowledge and practice.